A Hybrid CNN–LSTM Model for Emotion Prediction from Visual Data in Children - Vikas Jangra (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Emotion recognition is one of the crucial components of human-computer interaction that allows systems to respond intelligently to user emotions. In this paper, a hybrid framework for emotion recognition based on facial and gesture-based expression models is proposed. This framework utilizes a deep convolutional neural network for facial expression analysis and an LSTM for gesture recognition, thus providing state-of-the-art performance. A multimodal fusion technique combines the features of both modalities to boost the accuracy in emotion classification. Extensive evaluation was performed on benchmark datasets with an impressive accuracy of 87.5% to predict correct emotions across six basic emotions, a neutral state, valence, and nine complex emotions. Emotion recognition in children aged between 4 and 14 years is challenging since their emotional expressions are subtle and are in a developmental stage, with very few published works in this area. The novelty of this paper is a multimodal emotion recognition model for children, incorporating facial expressions and gestures, novel architecture, and multimodal input fusion, offering a richer and more context-aware emotion recognition framework, especially beneficial in dynamic child interaction environments. This work advances emotion recognition systems for younger populations with applications in education, child development, and healthcare.